THE ROLE OF PROBLEM-BASED LEARNING IN DEVELOPING ANALYTICAL AND CRITICAL THINKING IN SOCIAL SCIENCES EDUCATION - Tishabayeva Lola Arifovna (Western European Studies, 2025)
This article examines methods for teaching students how to solve social problems through the use of problem-based learning (PBL) technologies. It analyzes various strategies such as creating problem situations, discussions, analytical tasks, debates, brainstorming, and case-study methods, which enhance students’ independent thinking, ability to identify causeand-effect relationships, and capacity to make effective decisions regarding social issues. The study also highlights the role of PBL in developing social reasoning, critical thinking, and creative problem-solving skills.
Keywords: Problem-based learning; social issues; teaching methods